CHARACTERISTICS OF FEMALE MURDERERS IN POLAND - Karpuszenko, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The problems analysed in the study were inspired by the increasing number of reports on violent criminal acts committed by women as perpetrators. Therefore, it is worth analysing the motivations for committing the most serious crimes by women. Furthermore, the study took into consideration the determinants of committing the crimes that were connected with family and non-family environments of the criminals. The analysed factors included personality, experiences from the childhood, school and professional situation. The analyses discussed in the study attempted to determine a female murderer profile.